Nanoscale groove textured β-Ga2O3 by room temperature inverse metal-assisted chemical etching and photodiodes with enhanced responsivity - Kim, Munho; Huang, Hsien-Chih; Kim, Jeong Dong; Chabak, Kelson D.; Kalapala, Akhil Raj Kumar; Zhou, Weidong; Li, Xiuling (Applied physics letters, 2018)
β-Ga2O3 is an emerging wide band-gap semiconductor that holds great promise for next generation power electronics and optoelectronics. β-Ga2O3 based ultraviolet photodetectors have been the subject of active research for the last few years. However, no micro and nanostructure surface texturing has been demonstrated for efficient light management in β-Ga2O3 optoelectronic applications yet. We hereby present nanoscale groove textured β-Ga2O3 metal-semiconductor-metal photodiodes, enabled by the unique metal-assisted chemical etching (MacEtch) method at room temperature in liquid. Although the textured surface stoichiometry shows ∼10% oxygen deficiency which results in a reduced Schottky barrier height and increased dark current, clear enhancement of the responsivity is demonstrated, compared to the planar untreated surface. The realization of MacEtch's applicability to β-Ga2O3 opens the door for producing more sophisticated device structures for this material, without resorting to conventional dry etch and potential damage.